If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 8)(3x + -2) = 0 Reorder the terms: (8 + 4x)(3x + -2) = 0 Reorder the terms: (8 + 4x)(-2 + 3x) = 0 Multiply (8 + 4x) * (-2 + 3x) (8(-2 + 3x) + 4x * (-2 + 3x)) = 0 ((-2 * 8 + 3x * 8) + 4x * (-2 + 3x)) = 0 ((-16 + 24x) + 4x * (-2 + 3x)) = 0 (-16 + 24x + (-2 * 4x + 3x * 4x)) = 0 (-16 + 24x + (-8x + 12x2)) = 0 Combine like terms: 24x + -8x = 16x (-16 + 16x + 12x2) = 0 Solving -16 + 16x + 12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(-4 + 4x + 3x2) = 0 Factor a trinomial. 4((-2 + -1x)(2 + -3x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {-2, 0.6666666667}
| 2(0)+y=42 | | 1=y+3(y-9) | | 2.4=2.7 | | 25p^2-49p-2=0 | | 6(x+3)=3(2x+9)-9 | | 14x^2y^2+68xy^2-210y^2=0 | | 17k-12-4k-16k= | | 45z^2+56z-45=0 | | 4(0)+-2=-2 | | 10x-26=264 | | 3x-8x= | | 21b^2-114b-72=0 | | 87=5n-23 | | .12(18)+0.03x=0.06(24+x) | | 10x=264 | | 37=x+48 | | 18m^2-77m-18=0 | | 3(0)=-y+3 | | 3-8h=35 | | 13-x=-8 | | 3(-2)=-y+3 | | 8x^2-46xy+11y^2=0 | | 30-3x=2+x | | 2m^2+13m+10=0 | | 2m^2-10-4=4 | | .5x+12=27 | | 16x-3y=18 | | 12x^2+133x+11=0 | | 350-167+v=2v | | 68+2x-30=x+42 | | Y+(-8)=-23 | | 24-x=42 |